Sifat Fisikokimia Zat Pewarna dari Bunga Eceng Gondok (Eichhornia crassipes) yang Diekstrak dengan Metode Microwave Asissted Extraction (MAE) - Merynda Indriyani Syafutri; Filli Pratama; Gading Putra Yanda (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
SyafutriÂ et al, 2019. Physicochemical Properties of Colorant from Water Hyacinth Flower (Eichhornia crassipes) Extracted by Microwave Assisted Extraction (MAE) Method. JLSO 8(1):94-106.The objective of this research was to determine the effect of oven microwave power and extraction time on color intensity, anthocyanin stability, and antioxidant activity of colorant from water hyacinth flower (Eichhornia crassipes) extracted by microwave assisted extraction (MAE) method. The research was conducted at Agricultural Product Chemical Laboratory, Agricultural Technology Department, Faculty of Agriculture, Sriwijaya University. The experiment used a Factorial Completely Randomized Design with two factors and each treatment was repeated three times.Â The first factor was oven microwave power (100 watts and 300 watts) and the second factor was extraction time in oven microwave (1 minute, 2 minutes, and 3 minutes). The parameters were color intensity, anthocyanin stability, and antioxidant activity. The results showed that the oven microwave power and extraction time had significant effects on color intensity and antioxidant activity. The increasing of oven microwave power and extraction time increased a* value and antioxidant activity, and decreased b* value, significantly. The result also showed that the anthocyanin compounds was not stable with heating up to 105Â°C.